Effect of the duration of chronic low back pain on pain sensitivity of patients undergoing lumbar fusion surgery - Qian, Mei-ping; Dong, Mei-rong; Kang, Fang; Li, Juan (Pain medicine, 2021)
Background: chronic low back pain is a serious social problem. In recent years, patients who choose lumbar fusion surgery due to chronic low back pain has been increasing. Pre-existing chronic pain has been associated with severe postoperative pain. In this study, we have sought to prospectively analyze the association between the duration of chronic low back pain and pain sensitivity after lumbar fusion surgery. Methods: 400 patients who underwent lumbar fusion surgery were divided into three groups based on the duration of chronic pain. During the first postoperative day, the maximum pain scores of each patient day and night, the pain scores at the day of discharge, the consumption of postoperative analgesics and the length of hospital stay were recorded. Results: of 400 patients recruited, 369 patients completed the experiment. There was no significant difference in gender, age, height, weight, pre-operative pain at rest, and operation time in the three groups. During the day, the pain sensitivity of the three groups were 1.71 ± 0.66, 2.40 ± 0.74, 2.90 ± 0.80. During the night, the pain sensitivity of the three groups were 3.45 ± 0.81, 4.31 ± 1.06, 4.86 ± 1.05. At the day of discharge, the pain sensitivity of three groups were 1.26 ± 0.46, 1.47 ± 0.58, 1.96 ± 0.64. There were significant differences in pain sensitivity among the three groups during the day and night on the first postoperative day and at the day of discharge (p < 0.05). The length of hospital stay (7.31 ± 1.36 days, 8.82 ± 1.48 days, 9.60 ± 1.61 days) and analgesic consumption (25.04 ± 36.56 mg, 33.52 ± 24.04 mg, 45.15 ± 24.89 mg, morphine equivalent) were also significant differences (p < 0.05). Conclusion: we found the duration of chronic low back pain before lumbar fusion surgery affects patient’ postoperative pain sensitivity, consumption of analgesic drugs and hospital stay. The longer the preoperative chronic pain lasts, the higher the postoperative VAS score is, the more analgesic drugs were consumed, and the longer hospital stay is.